Everybody Counts or Nobody Counts - Paul A Craig; Michael N Kotlarchyk; Sophia Maggelakis (Academic Chairpersons Conference Proceedings, 2016)
Like most campuses, we constantly deal with change at RIT, ranging from policy to climate. We believe everyone needs to feel valued - “Everybody Counts or Nobody Counts," and are attempting to build a supportive culture that includes individual and group mentoring, funding opportunities, and recognition.
Keywords: mentoring; support; morale; recognition; climate